2022
DOI: 10.4047/jap.2022.14.4.223
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of clinical outcomes of implant restorations for posterior edentulous area: 3-unit bridge supported by 2 implants vs 3 splinted implant-supported crowns

Abstract: PURPOSE To compare the clinical outcomes of two types of implant restoration for posterior edentulous area, 3-unit bridge supported by 2 implants and 3 implant-supported splinted crowns. MATERIALS AND METHODS The data included 127 implant-supported fixed restorations in 85 patients: 37 restorations of 3-unit bridge supported by 2 implants (2-IB), 37 restorations of 3 implant-supported splinted crowns (3-IC), and 53 single restorations (S) as controls. Peri-implantitis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…(2013) reported that the plaque index and buccal pocket depth were higher in fixed partial dentures supported by three implants than bridges supported by two dental implants. The same authors also reported data confirming that over‐countered protheses increase the risk of peri‐implantitis, particularly at the level of implants located between the first and last (Yi et al., 2022). Ravidà et al.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…(2013) reported that the plaque index and buccal pocket depth were higher in fixed partial dentures supported by three implants than bridges supported by two dental implants. The same authors also reported data confirming that over‐countered protheses increase the risk of peri‐implantitis, particularly at the level of implants located between the first and last (Yi et al., 2022). Ravidà et al.…”
Section: Discussionmentioning
confidence: 85%
“…Initially, Yi et al. showed that external connection type implants had higher risk of peri‐implantitis (Yi et al., 2020), while in the latest publication, the same authors observed no statistically significant differences between the two types of connection (Yi et al., 2022). However, results showed that abutments fractured more frequently between components of the internal conical connection type, especially in prostheses that used gold cylinders (C‐Gold, S‐UCLA) (Yi et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations